Extraction And Characterization Of Moringa Oleifera Kernel Oil And Encapsulation By Coaxial Electrospinning - Toyin, Afolabi- Owolabi, Oluwafunke (2019)
Moringa oleifera (Mo) belong to the family Moringaceae with 14species, originated from South America, Africa and Indian Subcontinent. The kernel can be used for oil production, medicine, food supplement and water purification. In this study, four different types of extraction methods; namely cold pressing (CP), enzyme assisted cold pressing (EACP), enzyme assisted aqueous extraction (EAAE) and solvent extraction (SE) were used to produce oil from Mo kernel. The oil yield and oil recovery obtained were 8% and 23% for CP, 12% and 36% for EACP, 23% and 70% for EAAE and 23% and 99% for SE, respectively. The influence of different extraction methods on the microstructure of Mo kernel and flake were investigated. The physicochemical properties, antioxidant properties, oxidative activities and storage stability of the extracted oil were assessed. The fatty acid profile of the extracted oil was analysed using Gas Chromatography Mass Spectroscopy (GCMS), which reveal the monounsaturated fatty acid (MUFA) content range from 69 to 80%. Oleic acid found to be dominant in the Mo kernel oil, indicating its high stability towards oxidation. Thermal analysis of oil was also investigated using Differential Scanning Calorimetry (DSC). The result shows that different extraction method has significant effect on melting behaviour of Mo kernel oil. Based on the physicochemical properties, oxidative stability and fatty acid composition, CP oil was selected to be analyzed further by testing for its antioxidant properties and the effect of thermal degradation towards tocopherol content using High Performance Liquid Chromatography (HPLC).